Gut microbial metabolites: Shaping future diagnosis and treatment against gastrointestinal cancer - Hongyan Gou; Ruijie Zeng; Harry Cheuk Hay Lau; Jun Yu (Elsevier, 2024)
Gastrointestinal cancer is a worldwide health challenge due to its dramatically increasing prevalence and as a leading cause of cancer-related mortality. Increasing evidence has illustrated the vital role of gut microbes-derived metabolites in gastrointestinal cancer progression and treatment. Microbial metabolites are produced by the gut microbiota that utilizes both extrinsic dietary components and intrinsic host-generated compounds. Meanwhile, certain categories of metabolites such as short-chain fatty acids, bile acids, tryptophan, and indole derivatives, are linked to gastrointestinal malignancy. In this review, the major classes of microbial metabolites and their impacts on various gastrointestinal cancers including colorectal cancer, gastric cancer, and hepatocellular carcinoma, have been introduced. The application of microbial metabolites as predictive biomarkers for early diagnosis and prognosis of gastrointestinal cancer has also been explored. In addition, therapeutic potential of strategies that target microbial metabolites against gastrointestinal cancer is further evaluated.